(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article analyzes the calculation of the protective action time of personal respiratory protective equipment and proposed new calculations taking into account the liquidation of the fire or the search for the victim in high-rise buildings as well as the mass stay of people.